EFFECTIVE FACTORS IN RECRUITING AND IMPROVING EDUCATION DEPARTMENT STAFFS IN DISTRICT ONE OF TEHRAN: Life Sciences-Educational Management - SIMA FAGHANI SHOJA; MAHNOOSH ABEDINI (International Journal of Life Science and Pharma Research, 2022)
Recruiting capable and expert forces in Education Department is considered as one of the ways for improving educational level in every society. This study aims at evaluating effective factors in recruiting and improving staffs in Education Department in district one of Tehran. The main question of this study is how many factors can affect recruiting capable staff in Education Department? We used library research and field study methods as our research methods. The researcher has prepared a questionnaire; it is used as the research tool. Statistical Population consists of 520 people of managers and experts in Education Department (district one of Tehran). 220 people have been selected from among this population as research participants. They were chosen by a simple random sampling method based on Cochran formula. The reliability of this research through Cronbach’s alpha coefficient is equal to 0.786. It means that the reliability of the questionnaire is high in a remarkable manner. Our findings indicate that there is a positive and significant relationship among some of these factors including salaries and facilities, job security, job training and management factors such as organizational communications, also cultural factors and recruiting capable human resources. So it is necessary to analyze different functions of these factors in order to recruit expert and capable human resources for educational system.